Preparação e caracterização de complexos trinucleares de ferro(III) e cobalto(II) como potenciais precursores de estruturas inorgânicas estendidas e componentes antibacterianos - Lima, Bruno Ramos de (2020)
Frequently, synthetic inorganic chemistry performs a significant role in obtaining highperformance materials that exhibit increasingly specific behaviours. A highly versatile class of inorganic structures that continually gains prominence in academic works is the só-called “oxo-centred triangle structures”. These clusters, due to their intrinsic structural rigidity, are commonly explored in synthetic procedures which aim for their incorporation in polymeric materials such as, for instance, in the synthesis of MetalOrganic Frameworks (MOFs). The extended inorganic structures, both polymeric and supramolecular, are of great interest in studies related to the catalysis of reactions, sorption and separation of molecules, and the development of BioMOFs for release of drugs. The trinuclear units, on the other hand, by themselves, encompass a series of properties of indisputable relevance, highlighting in this work the study of antibacterial properties. Therefore, this work brings results regarding the synthesis and characterisation of four products: a one-dimensional coordination polymer, {[Co(μ-bzc)(H2O)2](bzc)·H2O}n (A), utilized as a starting material for obtaining the heterometallic trinuclear oxo-complex, [Fe2Co(μ3-O)(μ-bzc)6(H2O)3] (B); a trinuclear homometallic complex, [Fe3(μ3-O)(μ-hbzc)6(OH2)2(OHCH3)]Cl·3H2O·3pyz (C) and a linear trinuclear complex, [Co3(4,4’-bip)4(trim)2(H2O)10]·(4,4’-bip)·8(H2O) (D). Products that resulted in the formation of trinuclear oxo complexes (B and C) are unprecedented. The four structures were characterised by Single-crystal X-ray Diffraction (SCXRD) technique, revealing an excellent correlation between the proposed structural models and the experimental maps of the electronic density distribution of the unit cells from the R and Goodness-of-fit on F² indexes. The study of intermolecular interactions of the products was based on analysis of Hirshfeld surface in dnorm. The purity of the materials was confirmed by elemental analysis for the content of metals, C, H, N and by the Powder X-ray Diffraction (PXRD) technique. The thermal analysis for A, B and C products was based on TGA-DTG curves, that indicated better stability for the product (B), which starts the decomposition process at temperatures above 110 °C. All spectroscopic analysis data (IR, Raman, EPR and UV/Vis) corroborate with the particularities inherent to each structure. Antibacterial activity tests were performed for oxo-complexes B and C against strains of E. Coli (Gram-negative) and S. Aureus (Gram-positive). This study was based on the broth microdilution method for the determination of MIC and MBC, obtaining more promising results of MIC for the analysis of product B concerning strains of E. Coli. In terms of effectiveness, it was found that S. Aureus showed similar sensitivity between the tests with homometallic and heterometallic.